2020
DOI: 10.3389/fimmu.2020.606837
|View full text |Cite
|
Sign up to set email alerts
|

Protein Disulfide Isomerases Regulate IgE-Mediated Mast Cell Responses and Their Inhibition Confers Protective Effects During Food Allergy

Abstract: The thiol isomerase, protein disulfide isomerase (PDI), plays important intracellular roles during protein folding, maintaining cellular function and viability. Recent studies suggest novel roles for extracellular cell surface PDI in enhancing cellular activation and promoting their function. Moreover, a number of food-derived substances have been shown to regulate cellular PDI activity and alter disease progression. We hypothesized that PDI may have similar roles during mast cell-mediated allergic responses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
(121 reference statements)
2
10
0
Order By: Relevance
“…Thus, there is a great deal of research aimed at evaluating the use of probiotics as potential treatments for FA, and preclinical studies using probiotics have investigated the mechanisms leading to the amelioration of FA outcomes. The beneficial effects of probiotics on immune balance, intestinal barrier function [ 122 ], and structure of intestinal microbiota results in an effective alleviation of allergic responses [ 123 , 124 , 125 ]. Thus, germ-free mice administered with a mixture of three probiotic strains ( L. rhamnosus LOCK0900, L. rhamnosus LOCK0908, and Lactobacillus casei LOCK0919; isolated from stool samples from healthy infants) demonstrated stronger apical junctional complexes and adherent junctions in their enterocytes that resembled those of conventional mice and expressed higher levels of ZO-1 and occludin proteins than control germ-free mice [ 123 ].…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is a great deal of research aimed at evaluating the use of probiotics as potential treatments for FA, and preclinical studies using probiotics have investigated the mechanisms leading to the amelioration of FA outcomes. The beneficial effects of probiotics on immune balance, intestinal barrier function [ 122 ], and structure of intestinal microbiota results in an effective alleviation of allergic responses [ 123 , 124 , 125 ]. Thus, germ-free mice administered with a mixture of three probiotic strains ( L. rhamnosus LOCK0900, L. rhamnosus LOCK0908, and Lactobacillus casei LOCK0919; isolated from stool samples from healthy infants) demonstrated stronger apical junctional complexes and adherent junctions in their enterocytes that resembled those of conventional mice and expressed higher levels of ZO-1 and occludin proteins than control germ-free mice [ 123 ].…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“…Likewise, a recent study about the effect of three lactobacillus strains ( L. plantarum ZDY2013, L. plantarum WLPL04, and L. rhamnosus GG) on the intestinal barrier function of mice with FA showed an enhancement of TJ mRNA expression that was associated with the attenuation of allergic immune response and symptom severity [ 124 ]. In ZDY2013-treated animals, species in the families Ruminococcaceae and Lachnospiraceae were less abundant; two families that were previously reported significantly increased in the gut of infants allergic to cow’s milk [ 125 ].…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…PDIA3 identified following from DAT of MPN was found to be directly interacting with PRDX1 (found in both DAT of MPN and DMT of neuroblastoma cells), ACTB (found in DAT of MPN and both in DAT and DMT of neuroblastoma cells), and HSPD1. Recently, Krajewski and co-workers showed that protein disulfide isomerase catalytic activity plays an important role in the regulation of mast cell activation (115). They also showed that the inhibition of protein disulfide isomerase activity via pretreatment of mast cells with curcumin or other protein disulfide isomerase inhibitor such as PACMA-31 are able to supress the IgE mediated activation and various cytokines secretion (115).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Krajewski and co-workers showed that protein disulfide isomerase catalytic activity plays an important role in the regulation of mast cell activation (115). They also showed that the inhibition of protein disulfide isomerase activity via pretreatment of mast cells with curcumin or other protein disulfide isomerase inhibitor such as PACMA-31 are able to supress the IgE mediated activation and various cytokines secretion (115). Inouue et al showed that PRDX1 protects against allergenrelated hyperresponsiveness and Th2-type airway inflammation and involved in the inhibition of allergen-specific T-cell proliferation through immunological synapse (63).…”
Section: Discussionmentioning
confidence: 99%